Assesse the Health literacy in Multiple Sclerosis patients - Maryam Pooryaghob; Fariba Abdollahi; Tofigh Mobadery; Narges Hajishabanha; Zahra Bajalan (Mashhad University of Medical Sciences, 2018)
Background and objective: Health literacy is one of the major determinants of health and is one of the important factors in chronic diseases such as MS. The aim of this study was to evaluate the Health Literacy Association with health behaviors and health care utilization. Methods: This study was a cross-sectional study in which 100 patients with multiple sclerosis diseases selected by the convenience sampling in Qazvin hospital. Respondents completed the Rapid Estimate of Adult Literacy in Medicine, revised (REALM-R) and the Newest Vital Sign (NVS) instrument. For statistical analysis, we used logistic and ordinal regression and Kruskal-Wallis and Mann-Whitney tests. Results: Mean age of the subjects was 33/43±8/53 years. On the NVS, 63% of respondents had a high likelihood of inadequate literacy and 26% had borderline health literacy and 11% had adequate health literacy. On the Realm-r, 7% had inadequate literacy and 93% had adequate health literacy, Using logistic regression the frequency of alcohol consumption and using cigarette (p<0/05) and level of education (p-value=0/045) were associated with higher odds of having inadequately health literacy as assessed by the Realm-r. There was a significant correlation between Realm-r health literacy (p value=0/007) and NVS (p-value=0/005) with visits to the emergency room (ER), and hospitalizations in the last 6 months. Conclusion: Based on the results of the current study it is necessary to pay more attention to the health literacy level of the affected people and promote it in health programs and health promotion. Paper Type: Research Article.